Development of software for combining finite element and optical analyses - Kolobrodov, Valentin; Pozdniakov, Dmytro; Sokurenko, Vyacheslav; Tiagur, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2017)
In the process of development of numerous optical systems of aerospace designation, it is necessary to take into account deformations that arise in the optical and mechanical elements of the structure. Such deformations can occur due to loads, vibrations, impacts, temperature effects, and other factors. Their consideration in system development will enable prediction of influence of external factors on the final optical image quality. However, it is impossible to directly import results of finite element analysis into optical programs. A special computer program Deform was developed, which makes it possible to link programs for finite-element and optical analysis. The general idea is to determine parameters of the shape and spatial orientation of the spherical or aspherical "basic" surface, which is most closely approximated to the deformed surface for a specified set of surface points. Next, approximation of the deformation function of higher order is carried out. Operability of this software has been proven during development of means for a three-mirror anastigmattic quasi-orthoscopic lens. With the help of parametric simulation, a study was carried out on the influence of geometric parameters of lightening and fastening on deformation of the working surface of extra-axial segments of axisymmetric mirrors. As a result of this study, an option of lightening and fastening was selected, which minimized deformation of the working mirror surfaces. The results of simulation of impact of gravity on nonlightened and lightened mirrors, which was carried out in ANSYS Workbench, were then imported into ZEMAX optical analysis program for obtaining MTF charts of the system